Desarrollo de una pasta de cacao untable con propiedades nutritivas y funcionales a base de cacao (Theobroma cacao L.) sacha inchi (Plukenetia volubilis) y linaza Linum usitatissimum) - Escobar Barragán, Carlos Sebastián (2025)
In this research, it was proposed to improve the nutritional (protein) and functional (antioxidant) quality of spreadable cocoa paste with natural raw materials of little diffusion, such as cocoa, sacha inchi and flaxseed, for which a two-factorial design was applied. variables in a 3x2 factorial arrangement: Factor A (Purity of the cocoa paste) with three levels and Factor B (Mixture: sacha inchi-linseed) with two levels and two replicates, the best treatment is obtained based on the highest percentage of proteins and better antioxidant content. A sensory evaluation was applied to all treatments by a panel of 30 semi-trained tasters, where a significant difference was obtained in the general acceptability of T4(a2b2) and T5(a3b1), thus proving to be a viable product for its production. The data obtained from the percentage of protein by the DUMAS method show that the best treatment with the highest content was T4 (a2b2) with a value of (12.71%) which corresponds to the proportion of 42.9% cocoa powder + 42.9% sacha inchi flour + 14.3% flaxseed powder; However, the data obtained from the antioxidant content by the ABTS method show that the best treatment with the highest content was T5 (a3b1) with a value of (109.84 μmol ET/g) that corresponds to the proportion of 50.0% of cocoa powder + 25.0% sacha inchi flour + 25.0% flaxseed powder. Spreadable cocoa paste (T5): It has a fat amount of 12.86%, humidity percentage of 40.02%, ash percentage of 7.86% and fiber percentage of 25.27%. On the other hand, constant monitoring of production processes is essential to guarantee efficiency and quality in production; this comprehensive approach can lead to greater sustainability and competitiveness in the market.